INFLUENCE OF DIVIDEND PAYOUT RATIO, DEBT TO EQUITY RATIO, DECISIONS INVESTMENT AND PROFITABILITY ON FOOD AND COMPANY VALUE DRINK WHICH REGISTERED IN EXCHANGE EFFECT INDONESIA PERIOD 2019 – 2022 - Jessy Safitri Sitorus; Beby Adilla; Nursairah Dabutar; Agnes Hesty Demak Panjaitan; Wenny Anggeresia Ginting (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study aims to determine the influence of Dividend Payouts Ratio, Debt To Equity Ratio, Decision investment, Profitability  On the Company Value Population in study This is company consumption sub sector food and beverages for 2019 – 2022 listed on the Indonesia Stock Exchange (IDX) Which amount 31 company Based on research results and discussion about InfluenceDividend Payouts Ratio, Debt To Equity Ratio, Decision investment, Profitability  On the Value of Food and Beverage Companies Registered on Exchange Effect Indonesia Period 2019 – 2022. Can concluded as following: Variable Dividend Payouts Ratio (X1),variable Decision Investment (X3), And Profitability variable (X4) does not have a significant effect on variable Mark Company(Y) on Company Food and Drink Which Registered in Exchange Effect Indonesia 2019 - 2022. Variable Debt to Equity Ratio (X2)influential in a way significant to Company Value (Y) variable in Food and Beverage Companies Which Listed on the Stock Exchange Indonesia 2019 - 2022. Based on results study and discussion Which has obtained that the independent variable (X) is Dividend Payout Ratio, Debt To Equity Ratio, Decision Investment, And Profitability No influential in a way simultaneous tovariable dependent (Y) to Mark Company in Food and Beverage Companies Listed on the Stock Exchange Indonesia Period 2019 -2022.